The Role of Peer-to-Peer Coaching in Improving Performance and Quality Management of Health Service Workers - Elnardy, Mohammad Caesario; Widyasmoro, Adi; Supriyadi, Supriyadi; Zaharuddin, Zaharuddin (International Journal of Business, Law, and Education, 2025)
This study aims to analyze the role of peer-to-peer coaching in improving the performance and quality management of healthcare workers. Using quantitative methods, this study involved 10 health workers at the Indonesian Men's Clinic. Data were collected through questionnaires and analyzed using linear regression. The results showed that peer-to-peer coaching had a significant effect on improving individual performance but had no impact on the management of healthcare quality. This study provides practical contributions for healthcare managers to adopt a coaching approach as a human resource development strategy.